Variation of metabolic and bariatric surgery utilization by neighborhood socioeconomic status in Maryland - Oluwasegun Akinyemi; Terrence Fullum; Mojisola Fasokun; Kakra Hughes; Dahai Yue; Craig Scott Fryer; Jie Chen; Kellee White-Whilby (PLoS ONE, 2025)
Importance Metabolic and Bariatric Surgery (MBS) is a proven treatment for severe obesity, yet disparities in its utilization persist, particularly among socioeconomically disadvantaged populations. Objective To evaluate the association between neighborhood socioeconomic status (nSES) and MBS utilization in Maryland and assess whether this relationship varies by race and ethnicity. Design, setting, and participants A cross-sectional study using the Maryland State Inpatient Database (2018–2020), linked with the Distressed Communities Index (DCI). The study included adults aged ≥18 years with body mass index (BMI) ≥35 kg/m² who were eligible for MBS. Race/ethnicity was self-reported and categorized as non-Hispanic White, non-Hispanic Black, Hispanic, or Other. Main outcomes and measures The primary outcome was receipt of MBS. The primary exposure was nSES, measured using DCI quintiles (prosperous, comfortable, mid-tier, at-risk, and distressed). Multivariable logistic regression models estimated the adjusted odds of undergoing surgery, accounting for age, sex, race/ethnicity, insurance, comorbidities, obesity class, and urbanicity. Interaction terms tested effect modification by race. Results Of 169,026 eligible individuals, 11,963 (7.1%) received MBS. Most recipients were female (82.6%), with nearly equal representation of Black (46.9%) and White (46.1%) patients. A socioeconomic gradient in utilization was evident: individuals from distressed neighborhoods had 30% lower odds of receiving surgery (OR, 0.70; 95% CI, 0.64–0.76) compared to those in prosperous areas. Odds were similarly reduced for mid-tier (OR, 0.74; 95% CI, 0.70–0.79), at-risk (OR, 0.89; 95% CI, 0.83–0.96), and comfortable (OR, 0.89; 95% CI, 0.84–0.95) neighborhoods. Race moderated this association: across all DCI quintiles, Black individuals were more likely than White individuals to undergo surgery, with marginal effects increasing from 0.90% in prosperous to 2.10% in distressed areas. Conclusions and relevance MBS remains underutilized among eligible patients, especially those in socioeconomically disadvantaged neighborhoods. However, utilization patterns differ by race, with higher odds among Black individuals across all neighborhood strata. These findings highlight the need for targeted interventions to improve equity in obesity treatment access.